Association between asthma and lung function in adolescents born very preterm: results of the EPIPAGE cohort study. Issue 12 (31st March 2018) - Hadchouel, Alice; Rousseau, Jessica; Rozé, Jean-Christophe; Arnaud, Catherine; Bellino, Adèle; Couderc, Laure; Marret, Stéphane; Mittaine, Marie; Pinquier, Didier; Verstraete, Marie; Ancel, Pierre-Yves; Delacourt, Christophe
Abstract : Prematurity and bronchopulmonary dysplasia (BPD) affect long-term lung function. We studied the respiratory outcome of adolescents born very preterm and controls from the Etude EPIdémiologique sur les Petits Ages Gestationnels cohort and analysed their current lung function in relation to asthma symptoms (categorised in three age groups) from birth. In models including BPD, asthma at each age and confounding factors in the preterm group, BPD and preschool wheeze were the only independent variables associated with FEV1 . Preschool wheeze is an independent factor associated with FEV1 impairment in adolescents born very preterm. These results highlight the need for optimal management of early respiratory symptoms in preterm-born infants. Trial registration number: Results, NCT01424553 .